Hickory dickory dock and other silly-time rhymes (Norwalk, Conn. : Trudy Corp., 2005)
A collection of five familiar Mother Goose rhymes including "The House That Jack Built" and "Hickory Dickory Dock," with accompanying illustrations by various artists.
On board pages.
"A read-aloud book"--Cover.